Simulation Analysis on the Dynamics Performance of the Semi-Active Suspension System in High-speed EMUs - WANG Kai-ping; LI Jian-feng; XIANG Xian-hu; ZHAO Chang-long; LI Hai-tao (机车电传动)
A semi-active damper principle based on sky-hook theory was described. Taking CRH380A EMUs head car as studying object, influence of sky-hook damping coefficient and time delay of the system on the vehicle dynamics performance was analyzed. The results showed that: the greater the sky-hook damping coefficient was, the better lateral vibration performance of vehicle was, and the biggest system allowable time delay turned smaller. So, lateral vibration performance and system time-delay influence should be considered at the meantime for design of sky-hook damping coefficient. Compared with the passive suspension, the semi-active suspension improved lateral vibration isolated performance of car body obviously, the average improvement rate of which was more than 20%.